Nerve Growth Factor and Brain-Derived Neurotrophic Factor in COVID-19 - Carla Petrella; Giampiero Ferraguti; Luigi Tarani; Francesca Tarani; Marisa Patrizia Messina; Marco Fiore (Biology)
Neurotrophins (NTs) constitute a family of small protein messengers that play a fundamental role in both the central and peripheral nervous systems. In particular, the nerve growth factor (NGF) and the brain-derived neurotrophic factor (BDNF) play a subtle role in the survival, differentiation, and functioning of neuronal populations, as well as in the fine regulation of immune functions. The SARS-CoV-2 infection was characterized by a sequela of symptoms (serious respiratory pathology, inflammatory storm, neurological discomfort, up to the less serious flu-like symptoms), which caused, at the end of 2023, more than 7 million deaths worldwide. Despite the official end of the pandemic, the physical and psychological consequences are currently the object of scientific research, both acute and chronic/long-lasting (Long-COVID-19). Given the multifactorial nature of the outcomes of SARS-CoV-2 infection in adults and children, several studies have investigated the potential involvement of the NGF and BDNF systems in the pathology. This narrative review aims to summarize the most recent evidence on this crucial topic.